Endometriosis and femininity: a qualitative study - Hedyeh Riazi; Najmeh Tehranian; Saeideh Ziaei; Easa Mohammadi; Ebrahim Hajizadeh; Armin Firoozi (Payesh, 2014)
Objective(s): Endometriosis is a chronic and debilitating disease, which affects all aspects of the women’s life. The purpose of the present study was to explore the perception and experiences of endometriosis patients about femininity. Methods: A qualitative research was conducted to obtain data from 18 purposely selected endometriosis patients referring to a teaching hospital in Tehran, Iran. Data were collected by in-depth interviews and were analyzed using a conventional content analysis. Results: Seven categories and three main themes emerged from the participantschr('39') experiences. The themes were: 1) Feeling gynecologic disorders included three categories: menstrual disturbances, complaint of irritating cyst and pelvic infection problems, 2) Disruption in marital life included two categories: dyspareunia and infertility, 3) Disrupted social life included two categories: emotional and communicational disturbances and impairment in daily activities. Conclusion: The findings of present study showed that endometriosis affects femininity, which may have devastating consequences on individual, family and social life of affected person.